Experimental and theoretical investigation of the influence of tool paths and burnishing parameters on the quality of the burnished surface by magnetic assisted ball burnishing - Zsolt Kovács; Gábor Kónya; Balázs Markó; György Póka (Results in Engineering)
In this paper a new simulation method is presented that helps to qualify and compare different toolpaths and the influence of their parameters for magnetic assisted ball burnishing. Trochoidal and elliptically modified trochoidal toolpaths were analysed as well as the distance between the loops, overlap, burnishing feed and spindle speed. The most important surface features were measured and compared, primarily the surface roughness with Ra and Rz as well as the Rsk and Rku parameters, from which the tribological map can be constructed. Furthermore, by utilizing the oil retention capacity (A2 parameter) of the surface can be estimated. Moreover, the measurement of the Rpk and Rvk parameters, along with their ratio, allow conclusions about the wear process. Based on the experiments, it can be stated that magnetic assisted ball burnishing is an efficient method to improve the surface quality. However different settings are required to optimize the surface roughness, tribological characteristics and oil retention capacity, respectively. The proposed simulation method is based on image processing, in which the machined surface is converted to an image. The theoretical path of the balls’ centerpoint and the contact surface are assigned with pixels. The grayscale values theoretically correspond to the quality of machined surface. The measured surface roughness and Rsk, Rku values and the results of the simulation were in a good agreement. The proposed method allows to improve the toolpath planning for magnetic assisted ball burnishing because numerical and comparable results are proved.